Evaluation of Anchovy Fish Meal with or without Added Fish Solubles Compared to Other Specialty Protein Sources on Nursery Pig Performance - Ethan B. Stas; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 2,172 pigs (L337 × 1050 PIC; initially 11.4 lb) were used to evaluate anchovy fish meal with or without added anchovy fish solubles compared to other specialty protein sources on nursery pig performance in a commercial environment. At weaning, pigs were randomly allotted to 1 of 6 dietary treatments containing 6 different specialty protein sources added on an SID Lys basis. Dietary treatments consisted of diets with: 1) 7.0% enzymatically treated soybean meal (HP 300; Hamlet Protein; Findlay, OH); 2) 3.5% spray-dried bovine plasma (APC Inc, Ankeny, IA); 3) 5.0% microbially enhanced soybean meal (MEPro, Prairie Aquatech, Brookings, SD); 4) 5.2% microbially enhanced soybean meal with added anchovy fish solubles (TASA, Lima, Peru); 5) 4.85% anchovy fish meal (TASA Prime, TASA, Lima, Peru); and 6) 5.1% anchovy fish meal with added fish solubles (TASA Swine, TASA, Lima, Peru). Pigs were fed experimental diets in phases 1 and 2 based on feed budget with phase 1 fed at 5 lb/pig and phase 2 fed at 12 lb/pig. Experimental diets were fed for approximately 21 d after weaning and then all pigs were fed a common corn-soybean meal-based diet until the completion of the study. During the experimental period (d 0 to 21), pigs fed bovine plasma or anchovy fish meal had increased (P<0.05) ADG compared to pigs fed anchovy fish meal with solubles, with pigs fed other treatments intermediate. Pigs fed bovine plasma had improved (P<0.05) F/G compared to pigs fed anchovy fish meal with solubles, with pigs fed other treatments intermediate. Overall (d 0 to 42), a tendency was observed (P= 0.061) with pigs fed anchovy fish meal having numerically greater ADG compared to those fed the other treatments. On a per pig placed basis, there was a significant treatment effect (P= 0.032) where pigs fed anchovy fish meal had numerically higher ADG compared to the other treatments without significant mean separation. In conclusion, results of this trial indicated that anchovy fish meal as the sole specialty protein source can be utilized in nursery pig diets, but added fish solubles in combination with fish meal requires further investigation.
Keywords: anchovy fish meal; fish solubles; specialty protein sources; nursery pig